1996
DOI: 10.1076/phbi.34.5.344.13245
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties of Plant Flavonoids: An Overview

Abstract: Plant flavonoids are a large group of naturally occurring phenylchromones found in fruits, vegetables, grains, bark, roots, stems, flowers, tea and wine. While as much as several hundred milligrams are consumed in the average western diet, much work remains to be done on the absorption, distribution, metabolism and excretion of these compounds. A variety of in vitro and in vivo experiments have shown that selected flavonoids possess antiallergic, anti-inflammatory, antiviral and antioxidant activities. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(24 citation statements)
references
References 0 publications
3
20
0
1
Order By: Relevance
“…Although quercetin is able to markedly decrease the multiplicity of papillomas and the incidence of carcinomas after topical application to mouse skin, when orally administered it did not prevent UVB-induced skin carcinogenesis, probably due to the bioavailability problem [24]. Besides the described effects on carcinogenesis, quercetin is also an apt inhibitor of lipid peroxidation activity and exhibits anti-infective and anti-replicative activity against certain viruses [81,97]. However, regular diet cannot provide adequate amounts of quercetin compatible with several listed chemopreventive effects, although it is relatively easy to increase its total concentrations in plasma by the intake of quercetin-enriched foods or supplements [91].…”
Section: Sources Of Phenolic Compounds Their Antioxidant and Antimentioning
confidence: 99%
See 1 more Smart Citation
“…Although quercetin is able to markedly decrease the multiplicity of papillomas and the incidence of carcinomas after topical application to mouse skin, when orally administered it did not prevent UVB-induced skin carcinogenesis, probably due to the bioavailability problem [24]. Besides the described effects on carcinogenesis, quercetin is also an apt inhibitor of lipid peroxidation activity and exhibits anti-infective and anti-replicative activity against certain viruses [81,97]. However, regular diet cannot provide adequate amounts of quercetin compatible with several listed chemopreventive effects, although it is relatively easy to increase its total concentrations in plasma by the intake of quercetin-enriched foods or supplements [91].…”
Section: Sources Of Phenolic Compounds Their Antioxidant and Antimentioning
confidence: 99%
“…Quercetin and rutin at the same dose inhibit carcinogenesis by 50% and 30%, respectively [69]. Hesperetin, in comparison to quercetin, shows only anti replicative activity against some viruses [97].…”
Section: Sources Of Phenolic Compounds Their Antioxidant and Antimentioning
confidence: 99%
“…The best described property of almost all flavonoids is their antioxidative activity, which reported far exceeds that of well-known antioxidant vitamins (C and E) and carotenoids in in vitro and in vivo studies (Middleton, 1996). These are known to scavenge or inhibit the production of several kinds of free radicals and reactive oxygen species, which are the major cause of autoimmune and chronic inflammatory diseases in humans and animals like pulmonary hypertension syndrome (also called ascites) of broilers (Iqbal et al, 2002).…”
Section: Antioxidative Activity Of Flavonoidsmentioning
confidence: 99%
“…The activity was comparable to that of standard anti-inflammatory drug (Acetyl Salicylic Acid). It has been reported that flavonoids exert profound stabilizing effects on lysosomes both in vitro and in vivo experimental animals 11 , while tannin and saponins have the ability to bind cations and other bio molecules, and are able to stabilize erythrocyte membrane Following thrombolytic activity test of methanolic crude extract, it could be concluded that the extract of Z. mauritiana fruits showed moderate to good clot lysis activity.…”
Section: Discussionmentioning
confidence: 99%